Boronate Ligands in Materials: Determining Their Local Environment by Using a Combination of IR/Solid‐State NMR Spectroscopies and DFT Calculations. Issue 3 (27th December 2012) - Sene, Saad; Reinholdt, Marc; Renaudin, Guillaume; Berthomieu, Dorothée; Zicovich‐Wilson, Claudio M.; Gervais, Christel; Gaveau, Philippe; Bonhomme, Christian; Filinchuk, Yaroslav; Smith, Mark E.; Nedelec, Jean‐Marie; Bégu, Sylvie; et al.
Abstract Boronic acids (R‐B(OH)2) are a family of molecules that have found a large number of applications in materials science. In contrast, boronate anions (R‐B(OH)3−) have hardly been used so far for the preparation of novel materials. Here, a new crystalline phase involving a boronate ligand is described, Ca[C4H9‐B(OH)3]2, which is then used as a basis for the establishment of the spectroscopic signatures of boronates in the solid state. The phase was characterized by IR and multinuclear solid‐state NMR spectroscopy (1H, 13C, 11B and 43Ca), and then modeled by periodic DFT calculations. Anharmonic OH vibration frequencies were calculated as well as NMR parameters (by using the Gauge Including Projector Augmented Wave—GIPAW—method). These data allow relationships between the geometry around the OH groups in boronates and the IR and 1H NMR spectroscopic data to be established, which will be key to the future interpretation of the spectra of more complex organic–inorganic materials containing boronate building blocks.